Comparative studies on plasticized and unplasticized polyacrylonitrile (PAN) polymer electrolytes containing lithium and sodium salts - Md. Isa .K.B,; Othman .L,; Osman .Z, (Universiti Kebangsaan Malaysia, 2011)
Polymer electrolytes based on polyacrylonitrile (PAN) containing inorganic salts; lithium triflate (LiCF3SO3) and sodium triflate (NaCF3SO3) and ethylene carbonate (EC) as plasticizer were prepared using solvent casting technique. In this study, five systems of plasticized and unplasticized polymer electrolyte films i.e. PAN-EC, PAN-LiCF3SO3, PAN-NaCF3SO3 PAN-EC-LiCF3SO3 and PAN-EC-NaCF3SO3 systems have been prepared. The structural and morphological properties of the films were studied using infrared spectroscopy and scanning electron microscopy (SEM) while the conductivity study was done by using impedance spectroscopy. The infrared results revealed that interaction had taken place between the nitrogen atoms of PAN and Li+ and Na+ ions from the salts. SEM micrographs showed that the plasticized film, PAN-EC-NaCF3SO3 has bigger pores than PAN-EC-LiCF3SO3 film resulting in the film containing NaCF3SO3 salt being more conductive. On addition of salts and plasticizer, the conductivity of pure PAN increases to three orders of magnitude. The plasticized film containing NaCF3SO3 salt has a higher conductivity compared to that containing LiCF3SO3 salt. This result showed that the interaction between Li+-ion and the nitrogen atom of PAN was stronger than that of Na+-ion. The conductivity-temperature dependence of the highest conducting film from each system follows Arrhenius equation in the temperature range of 303 to 353 K. The conductivity-pressure study in the range of 0.01 - 0.09 MPa showed that the conductivity decreased when pressure was increased. This can be explained in term of free volume model.